2005
DOI: 10.1103/physrevb.71.195303
|View full text |Cite
|
Sign up to set email alerts
|

Shot-noise characteristics of triple-barrier resonant-tunneling diodes

Abstract: We have found experimentally that the shot noise in InAlAs-InGaAs-InAlAs Triple-Barrier Resonant-Tunneling Diodes (TBRTD) is reduced over the 2eI Poissonian value whenever their differential conductance is positive, and is enhanced over 2eI when the differential conductance is negative. This behavior, although qualitatively similar to that found in double-barrier diodes, differs from it in important details. In TBRTDs the noise reduction is considerably larger than predicted by a semi-classical model, and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…For given bias voltages the current flows through a stack of vertical coupled InAs quantum dots [16]. Therefore we deal with 3d-0d-0d-3d tunneling in contrast to the * Electronic address: Barthold@nano.uni-hannover.de above-mentioned experimental studies where the tunneling takes place through a two-dimensional subband [15]. The QDs were prepared by growing InAs on AlAs, the lattice-mismatch of InAs and AlAs causes the formation of the pyramidal QDs (Stranski-Krastanov-growth).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For given bias voltages the current flows through a stack of vertical coupled InAs quantum dots [16]. Therefore we deal with 3d-0d-0d-3d tunneling in contrast to the * Electronic address: Barthold@nano.uni-hannover.de above-mentioned experimental studies where the tunneling takes place through a two-dimensional subband [15]. The QDs were prepared by growing InAs on AlAs, the lattice-mismatch of InAs and AlAs causes the formation of the pyramidal QDs (Stranski-Krastanov-growth).…”
mentioning
confidence: 99%
“…It was shown that an impurity which is only weakly coupled to the leads can modulate the tunneling current through a nearby impurity leading to enhanced shot noise [14]. Super-Poissonian noise also has been studied experimentally for triple-barrier resonant tunneling diodes [15]. In this paper we study the shot noise properties of resonant-tunneling through vertically coupled zerodimensional systems, so-called quantum dots (QDs).…”
mentioning
confidence: 99%
“…The first two terms describe the contributions into nano-system conductivity of electron wave currents from RTS left side B The further calculation and analysis of spectral parameters (RE and RW) of electron QSS and its conductivity σ g is performed for In 0.53 Ga 0.47 As/In 0.52 Al 0.48 As RTS, often researched experimentally [3,4].…”
Section: Conductivity Of Mono-energy Electron Beam Of Cylindrical Twomentioning
confidence: 99%
“…Their elements are different nanostructures: quantum dots, wires and wells, in general and resonance tunnel structures (RTS), in particular. Growing interest to the latter is caused by the fact that after creation of the first quantum cascade (QC) lasers by J. Faist and F. Capasso [1,2], evident success is achieved in the design of active nano-structures [3,4], minimizing guided currents and reaching the maximal strength of electromagnetic radiation in the demanded range of frequencies (especially, in actual Terahertz ones).…”
Section: Introductionmentioning
confidence: 99%
“…4,15,16 Here we propose to use magnetic resonant tunneling diodes ͑RTDs͒ comprising coupled magnetic QWs and three nonmagnetic barriers, as spintronic devices offering large magnetocurrents ͑MCs͒. Corresponding nonmagnetic three barrier structures have been experimentally studied, [17][18][19][20] while electric field domain formation in magnetic multiple QWs was theoretically investigated in Ref. 21.…”
mentioning
confidence: 99%